Employee Engagement and Its Impact on Individual Work Behaviour and Discretionary Effort - Shanmugam, Priya (Journal of Contemporary Research in Management (JCRM), 2018)
Employee Engagement is a term used extensively in today’s business world and companies are in the forefront to bring about an engaged workforce. Since researches on employee engagement have proven its trail on increasing productivity (Harter et al. 2002), organizations are in the outlook to utilize any chance of creating an environment conducive for an engaged workforce. The dissertation aims at assessing the level of employee engagement and identifying its inter- relationship with individual work performance and discretionary effort. The study also aims at identifying the role of intrinsic motivation in the enhancement of psychological conditions of work and individual work performance. The Information Technology (IT) industry plays a critical role in sustaining growth and innovation in the country. In the last two decades, the Indian IT industry has contributed significantly to economic growth in terms of Gross Domestic Product (GDP), foreign exchange earnings and employment generation. However, the industry is encountering engagement and retention issues at present. There are different approaches to the construct of Employee Engagement and the role theory approach by Kahn (1990) is considered in this research. Employee’s self-in-role is measured and individual outcomes are emphasised. Since there are several research studies emphasising the business outcomes at large, there is no scope for organisational outcomes in this research. A structured questionnaire comprising all the requisite constructs solely for the present research based out of the already developed and validated research scales was framed. Based on the review of literature the research hypothesis was framed. The constructs used for the research were subject to reliability test using Cronbach’s Alpha to check for internal consistency. The Cronbach’s Alpha values for all the constructs are above 0.70 which showed acceptable reliability. The respondents were HR professionals in the IT companies in Bangalore sourced from LinkedIn SHRM Group and the research instrument was administered through online survey and e-mails. 548 completed responses were received, a response rate of 63% of the total questionnaires sent. The data was subject to analysis using SPSS and Structural Equation Modeling using Visual Path Least Square(PLS) Modeling. Inferential statistics like Paired sample t-test, Chi-Square test and correlation were used to bring out the effect of demographics on EE, IWP and DE. The inter-relationship between EE, IWP and DE was carried out and the hypotheses were tested using Visual PLS software. The study showed that the HR professionals in the IT industry have average to high level of engagement and most of them were engaged and non of the respondents were disengaged. The structural equation modeling showed that there existed a strong influence of psychological conditions of work – meaningfulness, availability and safety on employee engagement. Similarly, a strong relationship between employee engagement and discretionary effort was found. Employee engagement influenced productive work behavior and that in turn influenced discretionary effort. Intrinsic motivation was essential for the psychological conditions of work to improve and it also enhanced the contextual work performance of an individual. Counterproductive behavior being the negative aspect of an individual work performance impacted on the rise of intention to turnover. If an employee has to exhibit his discretionary effort he should be engaged and exhibit average too high level of individual work performance. For an employee to be engaged the psychological conditions must be present. The higher the employee engagement, the lower the intention to turn over. Highlevel of contextual performance will increase the level of discretionary effort. Intrinsic motivation can enhance the meaningfulness and availability in the psychological conditions of work. This study paved way for the understanding of the inter-relationship of employee engagement, individual work performance and discretionary effort. The companies can analyse which motivation factor will help to induce engagement and work performance. The limitations of the study and guidelines for future research were also discussed.